Optimizing Digital Communication in Dealing with Cybercrime for the Visually Impaired - Nurani Muksin, Nani; Yuningsih, Siska; Rosmi, Fitria; Pirmansyah, Khalid (Abdi Masyarakat, 2025)
The advancement of digital technology in the cyber era has opened up wide access to information, communication, and digital services. However, this progress has also given rise to challenges in the form of increasing cybercrime targeting vulnerable groups, including people with visual sensory disabilities. Limitations in receiving visual information make this group more vulnerable to threats such as phishing, theft of personal data, and digital fraud. In response to this, a community service activity entitled "Optimizing Digital Communication in Dealing with Cybercrime for People with Visual Sensory Disabilities" was held at the Raudhatul Makfufin Foundation, South Tangerang on June 15, 2025. This activity was attended by 37 blind participants aged 17-60 years, most of whom were active users of screen reader-based digital technology. The training method was carried out in a participatory manner through the delivery of materials, discussions, and simulations. The results of the training showed an increase in participants' understanding of various forms of cybercrime as well as the ability to recognize and anticipate digital crime modes. The training also equipped participants with secure digital communication skills, including the use of two-factor authentication and security applications. It is hoped that this activity can increase inclusive digital literacy and strengthen cyber resilience for the blind sensory disability community.